Garuda: Platform Optimalisasi Kolaborasi Antar Stakeholders Dalam Rangka Mendukung Collaborative Governance - Aldyansah Satria Utama; Elshaddai Hosanna Prasetyo; Toriqul Mujahidi Ashshobrul Karim (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
Indonesia is a country that has the fourth largest population in the world. According to data (kemendagri.com, 2021), it is recorded that Indonesia's population in 2020 is 272 million people and will continue to increase, especially with the prediction of a population spike (demographic bonus) in 2045. This increasingly massive population increase is feared to cause problems in more diverse countries in the years to come. In the process of solving problems, of course, it requires multi-sectoral roles from various parties, including the community. This research will explain the importance of collaboration and strengthening of NGOs/NGOs as a form of community participation that will be shaded by the concept of collaborative governance. This type of research is descriptive research using a qualitative approach related to the phenomenon raised. Based on the urgency of the problems that have been summarized from this research, it is found the urgency of the need for an applicative solution. The innovation is the GARUDAApp which is a manifestation of the principles of collaborative governance that is here to help answer various challenges in society that might occur in 2045 and in the years to come